THE INFLUENCE OF DIGITAL MARKETING ON SALES RESULTS OF TRADITIONAL TRADERS AT HORAS TAX PEMATANGSIANTAR CITY - Desi Sistiani; Amelia Oktavia Sidauruk; Hendri Mayanta Tarigan (Universitas Efarina, 2020)
Objective from study This is For know is There is the influence of digital marketing on results sale trader traditional in Pematangsiantar horas tax . Method research used _ is approach quantitative with questionnaires and manage data using SPSS. Results analysis regression linear simple showing that influential digital marketing variables positive and significant to results sales .